What Do We Really Know about the Role of Microorganisms in Iron Sulfide Mineral Formation? - Picard, Aude; Gartman, Amy; Girguis, Peter R. (Frontiers in Earth Science, 2016)
Iron sulfide mineralization in low-temperature systems is a result of biotic and abiotic processes, though the delineation between these two modes of formation is not always straightforward. Here we review the role of microorganisms in the precipitation of extracellular iron sulfide minerals. We summarize the evidence that links sulfur-metabolizing microorganisms and sulfide minerals in nature and we present a critical overview of laboratory-based studies of the nucleation and growth of iron sulfide minerals in microbial cultures. We discuss whether biologically derived minerals are distinguishable from abiotic minerals, possessing attributes that are uniquely diagnostic of biomineralization. These inquiries have revealed the need for additional thorough, mechanistic and high-resolution studies to understand microbially mediated formation of a variety of sulfide minerals across a range of natural environments.